Pendampingan Pembuatan Pupuk Organik di Dusun Klile Desa Karangasem Kecamatan Bulu Kabupaten Sukoharjo - Tri Hastini; Muhammad Uzzaironi; Wahyudiyanto Wahyudiyanto; Iftitah Juliarti; Ainur Komariah; Hamdan Kharisma (Universitas Veteran Bangun Nusantara, 2023)
ABSTRACT Karangasem Village, Bulu, Sukoharjo Regency has potential in the agricultural and livestock sectors. One of the service partners in Klile Hamlet livestock waste management. The aim of the service activities carried out by the PPK Ormawa team at Veteran Bangun Nusantara University is to improve the skills of partners in managing livestock waste, especially into compost. This activity was carried out in several stages, namely assistance and approaches in the form of discussions, counseling, demonstrations and direct practice related to making organic fertilizer from cow manure waste. The results of the service activities concluded that community knowledge regarding processing cattle waste increased by 90%, and the ability to practice making compost from cattle waste reached 80%